De la spécificité épistémologique du discours méta-glottodidactique1. Entre autonomie intellectuelle des chercheurs et leur appartenance à la communauté scientifique polonaise - Orchowska, Izabela (Studia Romanica Posnaniensia, 2017)
Meta-glottodidactic discourse is the area of academic discourse which enables one to develop and explicitly present general glottodidactic conceptions. This, however, is not a characteristic of didactic discourse concerned with foreign language teaching/learning and its optimization. It can be claimed that in their meta-glottodidactics discourse Polish language teaching specialists show their epistemological identity as scholars, which stems from their intellectual autonomy on the one hand and their glottodidactic community affiliation on the other. The present article talks about the discourse manifestations of Polish glottodidactics specialists’ intellectual autonomy, which are related to their epistemological choices and ways of justifying them. Given the lack of consensus about the basic epistemological issues within the glottodidactic community, scholars’ intellectual choices as well as their justifications can be varied and highly distinctive. In a qualitative comparative analysis of meta-glottodidactic discourse of two Polish glottodidactics specialists, the author of the article identifies the factors contributing to the diversity of Polish meta-glottodidactic discourse. She also attempts to explain why this particular type of discourse could encourage dialog within the Polish glottodidactic community, which might become a driving force behind the development of contemporary glottodidactics.